2008
DOI: 10.23917/forgeo.v22i1.4929
|View full text |Cite
|
Sign up to set email alerts
|

Akurasi Metode IDW dan Kriging untuk Interpolasi Sebaran Sedimen Tersuspensi

Abstract: ABSTRAK PENDAHULUAN Latar BelakangData di wilayah pesisir perlu dipelajari untuk berbagai kebutuhan seperti perencanaan pembangunan pelabuhan, pengembangan pariwisata dan budidaya pesisir seperti ikan kerapu, rumput laut dan terumbu karang buatan. Survei lapangan perlu dilakukan untuk mengumpulkan data. Dikarenakan kondisi alam yang terkadang buruk, wilayah cakupan yang luas dan keterbatasan waktu serta dana, maka survei dilakukan dengan mengambil beberapa titik sampel pengamatan. Untuk mengolah dan menganalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
30

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 3 publications
(1 reference statement)
0
10
0
30
Order By: Relevance
“…The assumption of this method is the value of interpolation will be more similar to the near sample data, besides that farther one. The weight will change linearly according to the distance of sample data [4]. The rainfall intensity in study area about 2591 -4276 mm/year that can be seen in Figure 8.…”
Section: Rainfallmentioning
confidence: 94%
“…The assumption of this method is the value of interpolation will be more similar to the near sample data, besides that farther one. The weight will change linearly according to the distance of sample data [4]. The rainfall intensity in study area about 2591 -4276 mm/year that can be seen in Figure 8.…”
Section: Rainfallmentioning
confidence: 94%
“…Metode interpolasi yang digunakan dalam penelitian ini adalah inverse distance weighted (IDW). Pramono (2008) menyatakan bahwa metode IDW memberikan hasil interpolasi yang lebih akurat dari metode kriging, hal ini ditunjukkan dengan nilai interpolasi metode IDW mendekati nilai minimum dan maksimum dari sampel data TSS. Affan (2012) dan Radiarta et al (2006) juga menyebutkan bahwa interpolasi data fisik wilayah pesisir lebih tepat menggunakan metode IDW karena tidak menghasilkan nilai melebihi data yang disampel.…”
Section: Analisis Dataunclassified
“…Inverse distance weighted, natural neighbor, spline, and kriging trend are the rules used in the interpolation. Furthermore, Booth and Mitchell [2,3]; Gorr and Kurland [13] and Pramono [30] have confirmed that Kriging rules has the advantages of unbiased properties, minimum variance, and it serves as a linear combination rather than observation. Kriging interpolation results from the data analysis of the soil bearing capacity in Kirkuk city is presented in Fig.…”
Section: Spatial Analysis Of Soil Bearing Capacitymentioning
confidence: 99%